Physical Demands during an elite female soccer game: Importance of training status - Kustrup, P.; Mohr, M.; Ellingsgaard, H.; Bangsbo, J. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To examine the activity profile and physical loading of elite female soccer players during match play and to study the relationship between training status and physical match performance.